A facile synthesis of branched graft copolymers via combination of RAFT self-condensing vinyl polymerization and aldehyde–aminooxy reaction. Issue 21 (7th June 2015) - Huang, Jianbing; Lin, Lvhuan; Liang, Hui; Lu, Jiang
<x xml:space="preserve">Abstract</x> A facile synthetic route to the branched graft copolymer BPDEM-g-PEO has been developed by combination of the RAFT-SCVP technique and aldehyde–aminooxy reaction.